Microfinance: where are we and where are we going?. Issue 7 (2nd October 2020) - Nogueira, Serafim; Duarte, Fábio; Gama, Ana Paula
ABSTRACT: This article provides a systematic literature review of growing research on microfinance, as promoted by scholars and policymakers in an entrepreneurial finance context. The results suggest promising opportunities for further research on microfinance in developed countries. Bibliometric analyses were used to identify three main dimensions of microfinance that guide academic research: social considerations, economic effects, and performance of microfinance institutions. Most literature focuses on developing countries, reflecting the success of microfinance as an instrument for promoting social and economic development. A keyword co-occurrence analysis reveals that financial inclusion and entrepreneurship domains remain empirically underexplored.